Aforisme Alquran dan Hermeneutika Terbuka: Interpretasi Ibn Ataillah atas Kehendak - Saifullah, Muhammad (Analisis: Jurnal Studi Keislaman, 2017)
This essay tries to explicate how Ibn Ataillah understands Qur’an within his popular book, al-Ḫikam. It is not merely his huge opus yet one of several books in which Indonesian Moslems like to learn and discuss. It covers the opened aphorisms stands on three entities, these are Qur’an, hadith, including some habits of Prophet Muhammad and subsequently I opt al-Ḫikam. As a sample, I am such demanded to come in through his interpretation concerning “will” or kehendak. Ibn Ataillah, as far as I feel, has deep conception with regard to “will” which is wallowed with dilemma. Sometime, he puts it as something freely owned by human, sometime on the contrary. By that conception, Ibn Ataillah covets an ideal figure such “superman”—to borrow Nietzsche phrase—as if. A super human that prefer living within dark surrounding to comfort, that is able to reflect his hard problems often and then solve it well. This article thus interests to look further how Ibn Ataillah’s hermeneutic model, particularly when composing al-Ḫikam. Who is his target audiences and how does it absorb to daily activities. The essay argues that Ibn Ataillah’s prescription in approaching Qur’an is going to a couple point, these are what I call as “creative abstraction” and an endeavor to reinvent Quranic mode or “reinvention of Quranic mode”.